Mechanism of Sulfur and Nitrogen Oxides Suppression in Combustion Products of Mixed Fuels Based on Coal and Wood; Combustion Science and Technology; Vol. 191, iss. 11 - Kuznetsov G. V. Geny Vladimirovich; Yankovsky S. A. Stanislav Aleksandrovich; Tolokolnikov A. A. Anton Andreevich; Zenkov A. V. Andrey Viktorovich (2018, 2018)
Title screen